Philosophical Approach of Reading Comprehension Test of Wattpad Readers and Writers Community - Merdeka, Pijar Hatinurani (EDUPEDIA Publisher, 2022)
Wattpad has become a popular application. It is not only a medium to read stories, but also it can be used as a medium to learn writing. For some people, including students, writing takes work. Thus, it declines students’ interest in writing. They might get some difficulties when they start to write and should get some kind of help, and using Wattpad can be a solution to their problem in writing learning. Besides easy to use, Wattpad is also provided several features that might help students to learn to write. On Wattpad, students can share their stories directly and get feedback from other users who will help them to tell their stories to lack thus, and they can revise them. Sharing their experiences and reading the other's story might help the student to improve their skills, not only in writing but also in their way of thinking. Therefore, the purpose of this article is to discuss how to use Wattpad to improve students’ writing skills and critical thinking skills.